QUALITATIVE EVIDENCE ON CHILLING EFFECTS—HOW USERS’ IMAGINARIES OF DATAVEILLANCE LEAD TO INHIBITED DIGITAL BEHAVIOR - Kappeler, Kiran; Festic, Noemi; Latzer, Michael (AoIR Selected Papers of Internet Research, 2023)
Our everyday life has become highly digitized, and all our online actions leave digital data traces that are automatically collected, aggregated, and analyzed. Emerging research shows that this dataveillance can lead to chilling effects on mundane and legitimate information and communication behaviors. However, the extent to which a sense of dataveillance deters individuals from freely engaging in legitimate digital behaviors remains empirically understudied. Therefore, we ask: How do internet users imagine dataveillance? And how does this perception lead to people limiting their digital behavior? To address these questions, we conduct qualitative semi-structured interviews with 15 individuals. Our results contribute to a better understanding of people’s imaginaries of dataveillance, as well as sources for these perceptions and reactions towards them in terms of chilled digital behaviors. We show how imagined sources of dataveillance can range from states to corporate actors and how knowledge about dataveillance can originate in news coverage on data scandals or own experiences. Also, we identify further legitimate, mundane behaviors in other life domains like participating in online dating and buying things online that are affected by a sense of dataveillance and have so far been neglected in research on chilling effects. These results contribute to an empirically founded understanding of the nature of a sense of dataveillance and resulting chilling effects on digital behavior. They provide the basis for a representative survey and a mobile experience sampling study as part of a mixed-methods research design investigating chilling effects on a population level.